Does periodontitis influence the risk of COVID‐19? A scoping review - Arunibha Ghosh; Betsy Joseph; Sukumaran Anil (Wiley, 2022)
Abstract Objective Research has shown that the novel severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) significantly influences the oral microbiome to expedite systemic diseases by invading harmful oral pathogens near and distant organs. To identify, explore, and map the possible mechanisms underlying periodontitis in severe coronavirus disease 2019 (COVID‐19) cases. Material and Methods Relevant articles published from December 2019 to February 2022 were identified and screened using keywords and inclusion criteria from various databases. Results This review sheds light on multiple pathways of periodontitis, the spread of periodontal infection and microbial metabolites to the lungs, and the dysregulated immune system with elevated cytokines, reactive oxygen species generation, nuclear DNA damage, and senescence, which have the potential to promote stronger viral attachment to host cells and the onset of COVID‐19 manifestation with increased severity and risk of mortality. In addition, the cytokine connection to SARS‐CoV‐2, T‐cell responses against periodontitis, its connection with COVID‐19, the role of host factors, and periodontal therapy have been discussed. Conclusions The relationship between COVID‐19 and periodontitis needs further investigation along with the development of alternative therapies to prevent periodontitis for better management and control of COVID‐19.